A Test Of Endogenous Growth Theories In Malaysia - Moh. Nasir Saukani; Abd. Ghafar Ismail; Rizaudin Sahlan (Economic Journal of Emerging Markets, 2002)
The aim of this paper is to investigate the determinants in per capita growth rate in Malaysia. The determinants draw on the recent endogenous growth theories and apply the Solow methodology to time series data from Malaysia, In our model, we develop a three different mode IS, i.e. Solow model, Mankiw Romer  Weil model and modifies Solow model. Our results indicate that, the growth rate of investment/GDP ratio, the growth rate of export trade over GDP ratio and the ratio of quasi liabilities of the financial system to GDP lead to improved growth performance.JEL classification: E23Keywords: endogenous growth model, international trade, government budget, and financial intermediation